Co-immobilization of PPL and GOx on DUT-5/PVDF hybrid membranes and catalytic activity in the cascade oxidation of glucose and styrene. (4th January 2023) - Hu, Defeng; Li, Rongzhong; Han, Yide; Meng, Hao; Zhang, Xia
Abstract : Co-immobilization of PPL and GOx on DUT-5/PVDF hybrid membranes was used in the cascade catalytic oxidation of glucose and styrene. Abstract : Currently, the co-immobilization of multi-enzymes on a solid carrier and their applications in cascade catalytic reactions are primarily studied. In this study, a MOF/polymer porous membrane composed of DUT-5 incorporated polyvinylidene fluoride (PVDF) is constructed and employed in the co-immobilization of porcine pancreatic lipase (PPL) and glucose oxidase (GOx) for the first time. The loading amounts of DUT-5 nanoparticles were varied to optimize the subsequent immobilization efficiency for the two enzymes. The adsorption conditions, isotherms and kinetics for both PPL and GOx were investigated systematically, and the optimum adsorption conditions were determined and used in the co-immobilization of the two enzymes step by step. It is interesting that the maximum adsorption amounts for the two enzymes in the co-immobilization process are similar to the results obtained in the single enzyme immobilization, which indicates the better compatibility of PPL and GOx in the hybrid membranes. The catalytic activities of the co-immobilized enzymes were evaluated using a cascade oxidation reaction, in which H2 O2 produced in the GOx-catalyzed oxidation of glucose worked as the oxidant in the subsequent oxidation of styrene. Further, the catalytic efficiency of the co-immobilized enzymes is compared to that of the mixed free PPL and GOx. The improved catalytic rates and better reusability of the co-immobilized enzymes highlight the broader applications of MOF-based membranes in the co-immobilization of two or more enzymes and the catalytic applicabality in the cascade organic reactions.